(untitled) (Islas, 2024)
Introduction: The Autograph album belonging to Zoe de la Torriente Brau adds to the list of documents preserved by the sisters of this illustrious family. The main objective of this article is to analyze this unique volume in relation to the life trajectory and intellectual contributions of its owner, aiming to enhance the understanding of this figure in connection with the cultural context of her time, and especially with the signatories of the dedications, many of whom are themselves pillars of 20th-century Cuban thought, with perspectives that also involve Puerto Rico and Spain. Methods: The research, which followed the historical-logical and inductive-deductive principles, was based on a documentary bibliographic review and qualitative content analysis—tools that revealed the connections between the album’s owner, her era, and the distinguished signatories who dedicated their thoughts to her. Results: An analysis of the composition of the volume, which spans from 1926 to 1996, shows that prose dedications are the most representative, followed by poems, drawings, musical scores, and photographs. The examination of the years and signatories, in dialogue with events from Zoe de la Torrente’s personal and professional life, as well as the Cuban cultural and social environment, made it possible to categorize four major groups of autographs, with the death of Pablo serving as a turning point in the organization of the signatures. Conclusions: This article has re-examined with an interpretive lens the voices and faces encapsulated in the distinguished signatures contained in this valuable document, a showcase of ideals, personalities, characters, codes of the time, and unique historical details that make it a small gem within the documentary collection of the family preserved by the Pablo de la Torriente Brau Cultural Center.